2017
DOI: 10.1590/1807-1929/agriambi.v21n8p513-518
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of vegetation index and soil properties in an integrated crop-livestock system

Abstract: A B S T R A C TThe knowledge of soil property spatial variability is useful for determining the rational use of inputs, such as the site-specific application of lime and fertilizer. The objective of this study was to evaluate the vegetation index and spatial variability of physical and chemical soil properties in an integrated crop-livestock system (ICLS). Soil samples were taken from a 6.9 ha area in a regular hexagon grid at 0-0.20 m depths. Soil P, K, Ca, Mg, and cation exchange capacity -CEC; base saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 15 publications
1
13
1
6
Order By: Relevance
“…On the other hand, the mapping of soil properties with higher variability can be less accurate than that of soil properties with lower variability. Trends in the variation of soil attributes obtained in this study are consistent with those observed by Bernardi et al (2014 and2016) for the same soil parameters. The lime recommendation data had shown a pure nugget effect which indicates a weak spatial dependence due the large variability.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, the mapping of soil properties with higher variability can be less accurate than that of soil properties with lower variability. Trends in the variation of soil attributes obtained in this study are consistent with those observed by Bernardi et al (2014 and2016) for the same soil parameters. The lime recommendation data had shown a pure nugget effect which indicates a weak spatial dependence due the large variability.…”
Section: Resultssupporting
confidence: 89%
“…Most researchers [17,18,[31][32][33], however, use normalized difference vegetation index (NDVI) as an auxiliary variable for the regression process. NDVI has been applied to many different aspects of rangeland ecology, but it has limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral signature of leaf tissue is correlated with its photosynthetic pigment content, its cell anatomical structure, and its water content. Because VIs are associated with plant biophysical characteristics, they are related to many crop agronomic characteristics, such as leaf area (Viña et al, 2010), plant nutrient and health status (Cammarano et al, 2014;Feng et al, 2017), and soil physical and chemical characteristics (Bernardi et al, 2017). VIs are commonly used for spatial analysis of vegetation development and may therefore also aid in selecting management practices in cultivated areas.…”
Section: Introductionmentioning
confidence: 99%